Застосування онтології задачі вибору для опису процесів взаємодії суб'єктів управління - Іохов, Олександр Юрійович; Малюк, Віктор Григорович; Сальніков, Олександр Михайлович; Новикова, Олена Олександрівна (Національний технічний університет "Харківський політехнічний інститут", 2021)
У статті доведено, що потребує вирішення проблема наявності протиріччя між збільшенням обсягу інформації, необхідної для прийняття рішень у сфері управління силами охорони правопорядку, і постійною вимогою щодо скорочення часу на її обробку в інформаційно-аналітичних системах. Мета статті полягає у підвищенні ефективності прийняття рішень в системі управління військового командування в умовах надзвичайного стану шляхом застосування онтології задачі вибору на основі сукупності семантично значущих результатів. Результати дослідження. Проаналізовані шляхи удосконалення механізмів інформаційно-аналітичного забезпечення системи управління військового командування в умовах надзвичайного стану. Використаний підхід до застосування онтології задачі вибору для прийняття рішень у сфері управління силами охорони правопорядку із застосуванням процедури інтеграції інформаційних ресурсів на основі бінарного відношення часткового порядку. Онтологічні системи, як результат зворотного відображення натуральних систем, забезпечують коректне агрегування різних тематичних процесів за рахунок формування структурованої сукупності інформаційних об'єктів-концептів предметної області, які визначаються як єдиний тип даних. За рахунок цього визначається онтологічний характер інтерпретації семантики контекстів об'єктів-концептів, які використовуються в процесі розв'язання задач в системі управління військового командування в умовах надзвичайного стану.

The ways of improving the mechanisms of information and analytical support of the command control system in the state of emergency are analyzed. The approach to the application of the ontology of the choice problem for decision-making in the field of law enforcement management using the procedure of integration of information resources based on the binary partial order relation is used. The purpose of the article is to increase the efficiency of decision-making in the management system of the military command in a state of emergency by applying the ontology of the choice problem based on a set of semantically significant results. Results of the research. Analysis and processing of large arrays of information in the field of military com mand management in a state of emergency should be carried out in an automated mode on the basis of a distributed software environment based on the principles of ontologies. Ontological systems, as a result of the inverse mapping of natural systems, provide the correct aggregation of various thematic processes through the formation of a structured set of information objects-concepts of the subject area, which are defined as a single type of data. The ontological representation of the contexts of units-concepts provides their integrated use in the process of solving complex tasks by the governing bodies of the command in a state of emergency. One of the constructive ways to integrate information resources as passive knowledge systems is to activate their concepts based on the process of forming thematic ontologies and combining these ontologies by building an ontology of the choice problem over them. The uniqueness of the ontology of the choice problem to any homotopy type allows to build the procedure of integration of information resources on the basis of a binary partial order relation. The partial order relation allows to reflect in an integrated way interaction of contexts of the notion-concepts defin-ing subjects of information resources. The contradiction between the increase in the amount of information needed for decision-making in the field of management of interdepartmental critical systems and the constant requirement to reduce the time for its processing in the information-analytical systems has been resolved.
Application of the ontology of the choice of selection to describe the processes of interaction of subjects of military communication management
Keywords: інформаційно-аналітична система; таксономія; множина тавтологій; бінарне відношення часткового порядку; information-analytical system; taxonomy; many tautologies; partial order binary relation